Changing Subjects, Moving Objects: Status, Mobility, and Social Transformation in Southeastern Europe, 1700–1850 - Vintila, Constanta (Balkan Studies Library, 2022)
This is a book about people caught between home and abroad, crossing imperial boundaries in southeastern Europe at the beginning of the modern age. Through a series of life stories, which the author reconstructs with the aid of many new sources, readers discover how certain men and women defined and adapted their loyalties and affiliations, how they fashioned their identities, how they enrolled their linguistic, political, economic, and social resources to build a family and a career. Travelling between Istanbul, Vienna, Trieste, Moscow, Bucharest, or Iaşi, individuals of different backgrounds built their networks across borders, linking people and objects and facilitating cultural transfer and material and social change.